Educação ambiental nas aulas de química do ensino médio: o tema água na abordagem CTSA - Rocha, Quezia Geane de Souza da (Universidade Federal de São Carlos, 2017)
Various environmental problems have been lived during the last decades, mainly caused by socioeconomic predominant models, confirming the needed of accomplished with Environmental Education, principally regarding school ambit, where the Environmental Education development must be responsibility of all subjects, that the highlight is Chemistry. Considering this problematic, this master degree work looked for didactic strategies to articulate the Environmental Education in the Basic Education Chemistry Classes, using water as the subject generator and the National Curricular Guidelines for Environmental Education as guiding, the strategies proposed were structured by Didactics Sequences . Three Didactics Sequences were building by study of National Curricular Guidelines for Environmental Education , São Paulo Chemistry Curriculum and the previous questionaries’ analysis applied in students participants of search. The Didactics Sequences elaborated were applied in the classroom and data collected by questionnaires, class reports, students’ activities, observation and audiovisual records. The data analyses show that the developed activities contributed for the student’s environment perception evolution from Naturalist for Globalizes, as well as insert social elements in contents which relate with Environment Education, however, the Didactics Sequences did not get successful to engage students regarding environment question, being one of the points to be improved on them. In relation of Chemistry Teaching, the classes dynamics allow diagnostic compression problems and students lacks, which in the traditional style of classes only would be revealed by writing evaluation, activities of final periods. The socioenvironmental contextualization allows to close the contents of the student realities and motivate their learning. The activities proportionated the development of abilities to realize searching and argumentation building, the responsibility and autonomy stimulation of students.
Environmental education in the high scholl chemistry class: the water theme in the STSE approach
Keywords: Ensino de química; Educação ambiental; Água; Chemistry teaching; Environmental education; Water; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM